Heat shock protein 90 and calcineurin pathway inhibitors enhance the efficacy of triazoles against Scedosporium prolificans via induction of apoptosis - Shirazi, Fazal (Microb Cell, 2014)
Scedosporium prolificans is a pathogenic mold resistant to current antifungals, and infection results in high mortality. Simultaneous targeting of both ergosterol biosynthesis and heat shock protein 90 (Hsp90) or the calcineurin pathway in S. prolificans may be an important strategy for enhancing the potency of antifungal agents. We hypothesized that the inactive triazoles posaconazole (PCZ) and itraconazole (ICZ) acquire fungicidal activity when combined with the calcineurin inhibitor tacrolimus (TCR) or Hsp90 inhibitor 17-demethoxy-17-(2-propenylamino) geldanamycin (17AAG). PCZ, ICZ, TCR and 17AAG alone were inactive in vitro against S. prolificans spores (MICs > 128 μg/ml). In contrast, MICs for PCZ or ICZ in combination with TCR or 17AAG (0.125-0.50 μg/ml) were much lower compared with drug alone. In addition PCZ and ICZ in combination with TCR or 17AAG became fungicidal. Because apoptosis is regulated by the calcineurin pathway in fungi and is under the control of Hsp90, we hypothesized that this synergistic fungicidal effect is mediated via apoptosis. This observed fungicidal activity was mediated by increased apoptosis of S. prolificans germlings, as evidenced by reactive oxygen species accumulation, decreased mitochondrial membrane potential, phosphatidylserine externalization, and DNA fragmentation. Furthermore, induction of caspase-like activity was correlated with TCR or 17AAG + PCZ/ICZ-induced cell death. In conclusion, we report for the first time that PCZ or ICZ in combination with TCR or 17AAG renders S. prolificans exquisitely sensitive to PCZ or ICZ via apoptosis. This finding may stimulate the development of new therapeutic strategies for patients infected with this recalcitrant fungus.